2022
DOI: 10.7717/peerj.12844
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metabolites in young and mature Docynia delavayi (Franch.) Schneid leaves using UPLC-ESI-MS/MS

Abstract: Docynia delavayi (Franch.) Schneid is a plant used both as food and traditional folk medicine. The leaves of D. delavayi are rich in polyphenols, plants with phenolic content are known to be extremely beneficial in terms of human nutrition. In the present study, we used metabolome technology (UPLC-ESI-MS/MS) to examine the young and mature D. delavayi leaves on metabolites changes, which were then analyzed and compared. As a result, 477 metabolites (including 111 flavonoids, 47 others (consisted of nine vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Various findings have shown that the composition of secondary metabolites differs in young and mature leaves [ 52 , 54 , 55 , 77 , 86 ]. Recent studies have found that Gingko biloba L. [ 52 ] and sugarcane [ 55 ] contain higher secondary metabolites in older leaves than in immature leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Various findings have shown that the composition of secondary metabolites differs in young and mature leaves [ 52 , 54 , 55 , 77 , 86 ]. Recent studies have found that Gingko biloba L. [ 52 ] and sugarcane [ 55 ] contain higher secondary metabolites in older leaves than in immature leaves.…”
Section: Discussionmentioning
confidence: 99%
“…YT, TX vs. SY and YT vs. SY comparisons suggested that the metabolite profile of TX was notably distinguishable from those of the other two varieties. It is strongly believed that flavonoids in plant tissues can improve the stress resistance of plants and protect them from abiotic stresses, such as UV-B radiation and drought ( Harborne & Williams, 2000 ; Xia et al, 2022 ). A previous study reported that flavonoids may function as antioxidants in response to excessive light exposure ( Tattini et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate statistical analysis was performed using ropls (Version1.6.2, , accessed on 8 March 2021) R package from Bioconductor on the Majorbio Cloud Platform ( , accessed on 8 March 2021). A PCA using an unsupervised method was applied to obtain and visualize an overview of the metabolic data, general clustering, trends, or outliers [ 54 ]. All metabolite variables were scaled to unit-variances prior to conducting the PCA.…”
Section: Methodsmentioning
confidence: 99%